A critical analysis of the independence of the interal audit function: evidence from Australia - Christopher, Joseph; Sarens, G.; Leung, P. (Emerald, 2009)
Purpose – This study aims to critically analyse the independence of the internal audit function through its relationship with management and the audit committee. Design/methodology/approach – Results are based on a critical comparison of responses from questionnaires sent out to Australian chief audit executives (CAEs) versus existing literature and best practice guidelines. Findings – With respect to the internal audit function's relationship with management, threats identified include: using the internal audit function as a stepping stone to other positions; having the chief executive officer (CEO) or chief finance officer (CFO) approve the internal audit function's budget and provide input for the internal audit plan; and considering the internal auditor to be a “partner”, especially when combined with other indirect threats. With respect to the relationship with the audit committee, significant threats identified include CAEs not reporting functionally to the audit committee; the audit committee not having sole responsibility for appointing, dismissing and evaluating the CAE; and not having all audit committee members or at least one member qualified in accounting. Originality/value – This study introduces independence threat scores, thereby generating analysis of the internal audit function's independence taking into account a combination of threats.